Photocatalytic Degradation of Malachite Green by Layered Double Hydroxide Based Composites - Nova Yuliasari; Alfan Wijaya; Risfidian Mohadi; Elfita Elfita; Aldes Lesbani (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Studies of LDH materials to be applied as photocatalyst for dye pollutant degradation have been developed. These interesting efforts are inseparable from the investigation of degradation performance and competitive synthetic methods. Composites based on Zn/Al and Mg/Al layered double hydroxides (LDHs) with ZnO and TiO2 were prepared by coprecipitation-impregnation method following by calcination at 300 °C to forms Zn/Al-ZnO, Mg/Al-ZnO, Zn/Al-TiO2, and Mg/Al-TiO2. Composites were characterized by XRD, FTIR, SEM and UV-DRS. Photodegradation of malachite green (MG) was carried out, after optimization of pH, catalyst loading and contact time in batch system under UV irradiation. XRD and spectroscopic data shows composites were successfully formed indicated by formation of both pristine materials. Degradation of malachite green showed that composites as photocatalyst have higher catalytic activity than pristine LDHs. LDH-ZnO composite have better activity, energy band gap and degradation reusability than LDH-TiO2. The Zn/Al-ZnO and Zn/Al-TiO2 composites degraded 97.1% and 96.3% MG, whereas the Mg/Al-ZnO and Mg/Al-TiO2 composites were able to degrade 99.8% and 98.6% MG, respectively. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).